Resilience-based interventions for parents of children with cancer: a systematic review - Sinaga, Sumiati; Abdul Mulud, Zamzaliza (International Journal of Public Health Science (IJPHS), 2025)
Childhood cancer diagnosis and treatment can have a negative impact, not only on the child but also on the parents. the study aims to systematically summarize the effectiveness of resilience-based interventions in parents of children with cancer. A systematic review was conducted on eight studies that met the eligibility criteria. Article searches were conducted using the PICO framework through six databases PubMed, Scopus, ScienceDirect, Proquest, WoS, and Clinical Key. The literature search followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Article searches were limited to publication years ranging from 2019 to 2023 using the keywords "resilience" "intervention" and "parents of children with cancer" and only in english. Studies have shown that interventions can improve parental resilience, reduce psychological distress, improve family functioning, and improve quality of life. These interventions also reduce parental hopelessness and improve coping. These outcomes are crucial for parents of cancer children to be resilient and adaptable, enabling them to support their children during treatment and care. The choice of intervention programs and approaches may vary depending on the needs of the parents. Therefore, the results of this literature review can be the basis for determining the approach used in providing nursing interventions aimed at helping parents of cancer children adapt to difficult situations.